Stored-grain insect management with insecticides: evaluation of empty- bin and grain treatments against insects collected from Kansas farms - Sehgal, Blossom (Kansas State University, 2013)
The insecticides, β-cyfluthrin and chlorpyrifos-methyl plus deltamethrin, are approved in the United States for treating empty bin surfaces. Chlorpyrifos-methyl plus deltamethrin and spinosad insecticides are approved for direct treatment of wheat. The efficacy of commercial formulations of β-cyfluthrin and chlorpyrifos-methyl plus deltamethrin at labeled rates was evaluated against adults of 16 field strains of the red flour beetle, Tribolium castaneum (Herbst); seven strains of sawtoothed grain beetle, Oryzaephilus surinamensis (L.); and two strains of the lesser grain borer, Rhyzopertha dominica (F.). Concrete arenas in plastic Petri dishes (9 cm diameter) were used to simulate the concrete floor of empty bins. The time for ~100% knockdown and mortality of adults of laboratory strains of the three species was first established by exposing them to insecticide-treated concrete surfaces for 1 to 24 h. Adults of field strains of each species were exposed to specific established insecticide-time combinations. Mortality of all species was lower than knockdown, suggesting recovery after seven days when placed on food. Chlorpyrifos-methyl plus deltamethrin did not control all R. dominica and most O. ]surinamensis field strains. β-cyfluthrin was extremely effective against R. dominica but ineffective against T. castaneum and O. surinamensis field strains, even at four times the high labeled rate. Field strains of R. dominica were highly susceptible to spinosad and chlorpyrifos-methyl plus deltamethrin at labeled rates on hard red winter wheat. Strains of T. castaneum and O. surinamensis were susceptible only to the latter insecticide. Dose-response tests with spinosad on the two least susceptible field strains of each species showed the lethal dose for 99% mortality (LD[subscript]99) for T. castaneum and R. dominica field strains were similar to that of the corresponding laboratory strains. Corresponding values for the two O. surinamensis field strains were significantly greater (~6 times) than the laboratory strain. The effective dose for progeny reduction (ED[subscript]99) of only one R. dominica field strain was significantly greater (~2 times) than that of the laboratory strain. The baseline susceptibility data of field strains of three insect species to spinosad will be useful for monitoring resistance development once this product is commercially released as a grain protectant.
Keywords: β-cyfluthrin; Chlorpyrifos-methyl plus deltamethrin; Spinosad; Stored-grain insects; Efficacy; Agriculture, General (0473); Entomology (0353)